The Pursuit of COVID-19 Biomarkers: Putting the Spotlight on ACE2 and TMPRSS2 Regulatory Sequences - Barash, Ayelet; Machluf, Yossy; Ariel, Ilana; Dekel, Yaron (Frontiers in Medicine, 2020)
Diverse populations worldwide are differentially affected by coronavirus disease 2019 (COVID-19). While socioeconomic background has been studied extensively, little is known about the genetic variation underlying this phenomenon. This study is aimed at examining the genetic basis behind the great discrepancies among diverse ethnic groups in terms of COVID-19 susceptibility for viral infection, disease prognosis, and mortality. To this end, in silico analysis of single-nucleotide polymorphisms (SNPs) within regulatory sequences of the human angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2)—the virus's gateway to host cells—and their plausible implications on expression levels was conducted. We provide indication that the variation in the human ACE2 and TMPRSS2 regulatory sequences is likely to be involved in and contribute to this phenomenon. SNPs that are abundant in the more susceptible populations introduce binding sites (BSs) for transcription factors or they may invalidate BSs for transcription repressor—both may enhance target gene (ACE2 or TMPRSS2) expression in the relevant target tissues. SNPs that are abundant in the more resistant populations may invalidate BSs for a transcriptional repressor or they may introduce BSs for a transcriptional repressor or initiator of mRNA degradation, which may reduce target gene expression levels. This aspect, when added to the socioeconomic factors, can be a cause for the divergent prevalence of the disease and the different mortality rates within diverse populations. This demonstration may call for a shift in the paradigm of searching for COVID-19 biomarkers, such that SNPs within regulatory sequences should be of high importance.